Prophetic Parenting As A Model For High School Students' Moral Development - Mutia Ake Prasong; Ruri Afria Nursa (Early Publishing, 2025)
Every adolescent desires to be recognized as proof of their identity.A teenager's great curiosity can sometimes lead to both good and bad things. They tend to have unstable emotions, so it's easy to fall into bad habits if no one controls a teenager. The living environment plays a major role in changing adolescent behavior. The parenting model that is applied to their children determines the formation of their morals. The role of the parenting model in the formation of morals has been exemplified by Rasulullah SAW. This article aims to explore and examine a model of moral formation for high school children through prophetic parenting. As for this research, it used a qualitative approach to the method of literature study. The results of this study indicate that prophetic parenting is the basis for parents' and teachers' efforts to educate adolescent morals. There are seven models of moral formation in adolescents, namely the internalization model, the exemplary model, the habituation model, the reward and punishment model, the attention model, the story model, and the advice model.